Theme Session C – Managing fisheries bycatch of threatened species ... - ICES (ASC 2023 - Theme session C, 2024)
Book of abstracts of theme session C: Managing fisheries bycatch of threatened species​Conveners: Eric Gilman (USA), Milani Chaloupka (Australia), Petri Suuronen (Finland)CM 15: Criteria for evaluating alternative management strategies for fisheries bycatch of threatened speciesCM 19: One study is not enough — Bayesian meta-synthesis of ocean-specific shark bycatch mortality ratesCM 61: Modernizing historic fishery effort distribution data to advise risk reduction for the North Atlantic right whaleCM 70: Post-release survival of mobulid rays in purse seine fisheriesCM 93: The potential of artificial intelligence to manage and reduce bycatchCM 98: Finding our way through the forest: using machine learning to improve catch estimationCM 104: Assessing selectivity and bycatch of endangered, threatened and protected species in the trolling and pole-and-line artisanal tuna fisheriesCM 139: Spatial overlap of threatened groundfish with commercial fisheries highlights conservation priority areas in Eastern CanadCM ...